Proposed approach for best practices of Shari'ah corporate governance in the Malaysian Islamic capital market - Kasim, Nawal; Htay, Sheila Nu Nu; Salman, Syed Ahmed (MAXWELL Scientific Publisher Corporation, 2014)
With the rapid growth of Islamic finance industry, the countries offering Islamic products should be preparing standards and guidelines to cater for current market needs to ensure that the industry is operating in a conducive environment. Since Malaysia strives to position itself as a hub for Islamic finance, it must ensure that it proactively works towards moulding the industry. With the needs of the industry, the Central Bank of Malaysia has issued the Shari'ah Governance Framework for Islamic banks and Takaful. This was necessary in view of the lack of guidelines best practices in Shari'ah corporate governance in the Malaysian Islamic capital market. To this end, this study seeks to determine the approach best suited to establish a framework of Shari'ah corporate governance for listed companies in Malaysia. The interview results show that the hybrid approach is best suited to provide the general guidelines as a reference while accommodating the flexibility of Islamic law. © Maxwell Scientific Organization, 2014.